School Supervisors in Enhancing Education Quality via the School Accreditation Process - Hermawan Raharjo Putro; Ahmad Muhibbin; Sigit Haryanto (LPPM Undiksha, 2024)
Improving the quality of education is a top priority. However, the current problem is that many schools still need to pay more attention to the quality of education. Based on this, this research aims to analyze the influence of school supervisors in improving the quality of education through the school accreditation process. The approach applied in this research is qualitative, while the data collection technique used combines qualitative and quantitative. The subjects of this research were 40 people (20 teachers and 20 education service staff). The methods used to collect data are document study, observation, and interviews. The instrument used in data collection was a questionnaire sheet. Quantitative data analysis techniques are applied to analyze the quality of school supervisors' performance, including three stages: data condensation, data display, and (3) Conclusion/verification. Quantitative Data Processing is carried out by providing questionnaire instruments and the urgency of handling each variable. The results of this research conclude that there is a gap in the role of school supervisors. This indicates that the school supervisor needs to be more optimal in carrying out his role as a supervisor. To overcome the gap in the role of school supervisors there are several efforts to eliminate the gap that occurs between education staff and teachers regarding the role of school supervisors, including increasing supervision and coaching, strengthening effective communication and collaboration, providing adequate support, developing the skills of school supervisors, and conducting evaluations and continuous improvement.